VD_FINDINFO HC / 2014 / 890 vom 5. September 2014 - VD Tribunal cantonal (2014)
DÉCISION ÉTRANGÈRE, RECONNAISSANCE DE LA DÉCISION, DROIT TRANSITOIRE, COMMUNICATION, DEMANDEACTION EN JUSTICE | 34 ch. 2 CL (2007), 63 ch. 1 CL (2007), 63 ch. 2 CL (2007), 327a CPC (CH)